Molybdenum Carbide‐PtCu Nanoalloy Heterostructures on MOF‐Derived Carbon toward Efficient Hydrogen Evolution. Issue 51 (28th October 2021) - Zhang, Chengtian; Liu, Qian; Wang, Pengyan; Zhu, Jiawei; Chen, Ding; Yang, Yue; Zhao, Yufeng; Pu, Zonghua; Mu, Shichun
Abstract: In this study, PtCu‐Mo2 C heterostructure with charge redistribution is investigated via first‐principles theoretical calculations. Mo2 C can promote the formation of the electron‐rich region of PtCu as an active site, displaying an optimized adsorption behavior toward hydrogen in terms of reduced thermodynamic energy barriers. Owing to the attractive density functional theory calculation results, the PtCu‐Mo2 C heterostructure is fabricated via carbonization of the unique metal–organic framework (MOF) followed by the replacement reduction reaction for the first time. Owing to its swift kinetics and outstanding specific activity, it exhibits high hydrogen evolution reaction (HER) catalytic activity (26 mV @ 10 mA cm −2 ) and superior mass activity (1 A mgPt −1 at −0.04 V) in acidic media, which is approximately six times that of commercial Pt/C catalysts. The perception of the intrinsic activity origin of the alloy with an excellent structural support can guide the development of Pt‐based and other alloy catalysts in future. Abstract : Metal–organic framework derived Mo2 C‐PtCu nanoalloy heterostructures on carbon exhibit superior hydrogen evolution reaction (HER) catalytic performance, which opens up an available direction for development of highly efficient Pt‐based and other alloy catalysts toward HER and other electroctalysis.